Clinical neuropsychology: Status in Western countries and potential in Lithuania - Grambaitė, Ramunė; Bieliauskas, Linas; Grušauskienė, Evelina; Bagdonas, Albinas (Psichologija, 2019)
We present an overview of the development of clinical neuropsychology, the current status of the specialty of clinical neuropsychology in Western countries, and the possibilities of developing this specialty in Lithuania. The main duties of a clinical neuropsychologist are to perform neuropsychological assessments and clinical interventions. Clinical neuropsychologists working within health care are professionals who offer services to patients across the lifespan with cognitive and behavioral/emotional symptoms related to neurological, developmental, and psychiatric disorders. Specialists of clinical neuropsychology are needed in neurology and psychiatry clinics, in centers of mental health and rehabilitation, and institutions of psychological assessment and education of children. The specialization models of clinical neuropsychology in Europe and North America are similar in their content and requirements for courses and practice. Nevertheless, specialist education in most of European countries is related to clinical training and not an academic degree, as it is in the USA and Canada. The duration of specialist education in clinical neuropsychology in Europe varies, but this education can only be started after acquiring a Master’s degree in most of the European countries. The regulation of the specialty of clinical neuropsychology in Europe also varies. In some countries, this specialty is fully legally regulated, and in some countries not regulated at all. For specialization in clinical neuropsychology, the license of a psychologist, enabling an individual to work in the health care system of the country, is required in most Western countries. Taking into consideration the Scandinavian experience, it can be expected that the planning of specialization studies in Lithuania would be easier if the licensing of psychologists would be regulated. Today, traditional specializations of psychology in Lithuania may be obtained through Master’s degree studies, i.e., a specialized Master’s diploma compensates a license and any need of further specialization. This Lithuanian tradition is not in accord with the EuroPsy politics of obtaining a diploma: a Master’s diploma is acquired within 6 years of studies, and, after these studies, specialization is continued for a few more years (participation in specialized courses, performance of supervised practice). The model of specialization in clinical neuropsychology in Lithuania should be developed in accordance with international standards of neuropsychology, which are in constant development. In Western countries, the knowledge and skills of clinical and health psychology are considered to be an important part of the specialist education in clinical neuropsychology. Therefore, two years of Master’s studies in clinical neuropsychology would not be sufficient when preparing competent clinical neuropsychologists, unless it is combined with a supervised neuropsychological practice of a defined duration. A doctoral degree is required for neuropsychological practice in the USA, but it is usually not required in Europe. In Lithuania, such a tradition for other specializations of psychology does not exist either, which suggests that a doctoral degree should not be necessary for the specialty of clinical neuropsychology as well. Nevertheless, like in Western countries, supervised clinical neuropsychological practice should be a necessary part of the specialists’ education in clinical neuropsychology.
Keywords: clinical neuropsychology; neurology; neuropsychological assessment; neuropsychological intervention; education in clinical neuropsychology